Association of changes in inflammation with variation in glycaemia, insulin resistance and secretion based on the KORA study. Issue 8 (2nd October 2018) - de las Heras Gala, Tonia; Herder, Christian; Rutters, Femke; Carstensen‐Kirberg, Maren; Huth, Cornelia; Stehouwer, Coen D.A.; Nijpels, Giel; Schalkwijk, Casper; Flyvbjerg, Allan; Franks, Paul W.; Dekker, Jacqueline; Meisinger, Christa; et al.
Abstract: Aims: Subclinical systemic inflammation may contribute to the development of type 2 diabetes, but its association with early progression of glycaemic deterioration in persons without diabetes has not been fully investigated. Our primary aim was to assess longitudinal associations of changes in pro‐inflammatory (leukocytes, high‐sensitivity C‐reactive protein (hsCRP)) and anti‐inflammatory (adiponectin) markers with changes in markers that assessed glycaemia, insulin resistance, and secretion (HbA1c, HOMA‐IR, and HOMA‐ß). Furthermore, we aimed to directly compare longitudinal with cross‐sectional associations. Materials and methods: This study includes 819 initially nondiabetic individuals with repeated measurements from the Cooperative Health Research in the Region of Augsburg (KORA) S4/F4 cohort study (median follow‐up: 7.1 years). Longitudinal and cross‐sectional associations were simultaneously examined using linear mixed growth models. Changes in markers of inflammation were used as independent and changes in markers of glycaemia/insulin resistance/insulin secretion as dependent variables. Models were adjusted for age, sex, major lifestyle and metabolic risk factors for diabetes using time‐varying variables in the final model. Results: Changes of leukocyte count were positively associated with changes in HbA1c and HOMA‐ß while changes in adiponectin were inversely associated with changes in HbA1c . All examined cross‐sectional associations were statistically significant; they were generally stronger and mostly directionally consistent to the longitudinal association estimates. Conclusions: Adverse changes in low‐grade systemic inflammation go along with glycaemic deterioration and increased insulin secretion independently of changes in other risk factors, suggesting that low‐grade inflammation may contribute to the development of hyperglycaemia and a compensatory increase in insulin secretion.